Decolonizing Psychology and Integrating a Critical Hermeneutic Framework to Heal Racial Disunity in Faith-Based Clinical Programs - Pak, Jenny Hyun Chung (Journal of psychology and christianity, 2023)
In our efforts to overcome cultural blindness and decolonize Western psychology, the cultivation of critical consciousness in practitioners is imperative, especially as it relates to culture and race. At its core, critical reflexivity involves exploring one’s assumptions by examining and questioning their historical and cultural origins and developing alternative ways of acting. This article attempts to address the problem of racial disunity by focusing on faith-based clinical psychology programs as a lever of change. In the active work towards racial unity within Christian institutions, we propose examining the lasting effects of Western colonialism and engaging in the decolonization of psychology from a critical hermeneutic framework by focusing on (a) raising critical consciousness, (b) engaging in critical reflexivity, (c) creating spaces for "thickness" and safety, and (d) empowering equal dialogic relationships. By accounting for the historical and cultural context of individuals, it then becomes possible to foster unity through practicing critical reflexivity and an embodied model of integration that provides spaces to truly address barriers to God’s mission and purpose, atonement, lament, and God image. Through recognizing the history of racism and structural power dynamics, faith-based clinical programs can actively create more inclusive environments for students of color and build trusted relationships that lead to true transformation and healing.